Vejrforholdene i Landbrugsaaret 1947—48. (Fra 1. Oktober 1947 til 30. September 1948). - Hansen, H. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1947—48. (Fra 1. Oktober 1947 til 30. September 1948).